Homogeneous alignment of liquid crystals on low-temperature solution-derived gallium oxide films via IB irradiation method. Issue 3 (19th February 2016) - Jang, Sang Bok; Heo, Gi-Seok; Kim, Eun-Mi; Park, Hong-Gyu; Lee, Ju Hwan; Jung, Yoon Ho; Jeong, Hae-Chang; Han, Jeong-Min; Seo, Dae-Shik
ABSTRACT: In this paper, solution-derived gallium oxide (GaO) films are fabricated for the homogeneous alignment of liquid crystals (LCs) after an ion-beam (IB) irradiation process. GaO thin films are prepared under a variety of temperatures and different IB irradiation intensities, and the physicochemical performances of the fabricated GaO thin films are analysed using a UV-vis spectrometer, an atomic force microscope, and X-ray photoelectron spectroscopy. A higher transmittance of 85.40% from GaO thin film is obtained compared with that of polyimide (PI) film (83.52%), which indicates the feasibility for a GaO thin layer to substitute for a conventional PI layer as an alignment layer. LCs are found to align on the GaO thin film after pre-baking at 100°C and homogeneous and uniform low-IB intensity irradiation. We also determined the electro-optical (EO) characteristics of the twisted nematic (TN) cells fabricated with GaO thin layers and found them to be similar to those of cells fabricated with PI layers. Overall, GaO films achieved via the IB irradiation method are promising LC alignment layers due to the method's low-temperature solution-derived process. GRAPHICAL ABSTRACT: